The Effect of Price, Promotion, and Packaging towards Purchase Intention of Stacks Food in Surabaya - Lou, Daniel Christian (International Business Management - Universitas Ciputra, 2021)
As the food and beverage industry is growing in Indonesia and businesses are getting more competitive and challenging. This research was conducted to understand the effect of price, promotion, and packaging towards purchase intention of Stacks Food. This research was conducted from September 2020 – December 2020. This research was conducted using the quantitative method and the Likert scale. The population of this research are those located in Surabaya with the minimum age of 16 years old. The sample size is 100 respondents selected using non-probability sampling and purposive sampling method. The data are then analysed with SPSS Statistics 26 using multiple regression analysis. The multiple regression analysis shows that price (Sig value = 0.004), promotion (Sig value = 0.002), and packaging (Sig value = 0.000) have significant influence towards purchase intention. Thus, it can be concluded that price, promotion, and packaging have significant influence towards purchase intention of Stacks Food in Surabaya. Keywords: price; promotion; packaging; purchase intention